2022
DOI: 10.1016/j.celrep.2021.110224
|View full text |Cite
|
Sign up to set email alerts
|

HsfA7 coordinates the transition from mild to strong heat stress response by controlling the activity of the master regulator HsfA1a in tomato

Abstract: Plants respond to higher temperatures by the action of heat stress (HS) transcription factors (Hsfs), which control the onset, early response, and long-term acclimation to HS. Members of the HsfA1 subfamily, such as tomato HsfA1a, are the central regulators of HS response, and their activity is fine-tuned by other Hsfs. We identify tomato HsfA7 as capacitor of HsfA1a during the early HS response. Upon a mild temperature increase, HsfA7 is induced in an HsfA1a-dependent manner. The subsequent interaction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 44 publications
(64 reference statements)
2
17
1
Order By: Relevance
“…HsfA1a is a constitutively expressed gene mainly regulated at posttranslational level (El-shershaby et al 2019;Mesihovic et al 2022). We also confirmed that HsfA1a transcript levels do not significantly change in response to TUN treatment (Supplemental Fig.…”
Section: Effect Of Hsfa1a Overexpression or Suppression On The Tolera...supporting
confidence: 78%
“…HsfA1a is a constitutively expressed gene mainly regulated at posttranslational level (El-shershaby et al 2019;Mesihovic et al 2022). We also confirmed that HsfA1a transcript levels do not significantly change in response to TUN treatment (Supplemental Fig.…”
Section: Effect Of Hsfa1a Overexpression or Suppression On The Tolera...supporting
confidence: 78%
“…Cultivated tomatoes have large apical bud structure which may affect meristem temperature, which has been thought to be drastically impacted by apical bud structure and function [ 53 ]. Since HsfA7 is a capacitor of the central regulator of HsfA1 during the early heat stress response [ 50 ], its distinctive expression response may be caused by the putative difference in meristem temperature between Moneymaker and its ancestral relatives. Notably, plant temperature is one of the key modulators controlling plant development and heat stress transcription factors (i.e., HSFA2 in Arabidopsis) have been shown to regulate heat stress-related SAM development [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…To breed new varieties suitable for growing in suboptimal environments under the current trend of global climate change, it is important to understand how domestication and breeding has changed phenotypic plasticity. Notably, recent studies have revealed that gene expression regulated by AS plays crucial roles in plant response to changing environments, especially varying temperature [ 26 , 30 , 46 , 47 , 48 , 49 , 50 ]. In tomatoes, intronic polymorphisms affecting AS of the heat stress transcription factor HsfA2 have been found to be associated with the difference in heat stress response between cultivated tomato and wild species [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the acclimation of tomato to HS is dependent on the AS of HsfA2 ( Hu et al, 2020b ). Worth mentioning, tomato HsfA7 is subjected to the same regulatory control like HsfA2, further highlighting the important of AS for thermotolerance ( Mesihovic et al, 2022 ).…”
Section: Gene-specific Studies Showcasing the Significance Of Alterna...mentioning
confidence: 99%